NUR ROFIAH'S METHOD OF CRITICAL INTERPRETATION IN LINGKAR NGAJI KGI - Yuliana Jamaluddin (SYAHADAH : Jurnal Ilmu al-Qur'an dan Keislaman, 2022)
Nur Rofiah is one of the female Muslim scholars in Indonesia who concerned in the field of interpretation and gender justice . Her interpretation critics method could be seen through her study in recent years. It is called Lingkar Ngaji KGI ( Islamic Gender Justice), offline or online . This study will focus on KGI Regular online that is thematically, especially on the Instagram account @ngaji_kgi. This study wants to know how the method used by Nur Rofiah in criticizing gender biased religious interpretations that have been developed massively. In her critics, Nur Rofiah classifies verses which talk about woman into three verse groups. They are starting point verse, intermediate target verse , and final destination verse. These three groups of verses need to be understood well, in order to determine whether the instructions are temporal or universal. Regardless from these three groups, there is basic principle since the beginning carried by the Qur'an and the Prophet Muhammad as treatise carrier. The basic principle is awareness related woman humanity, which started moving from lowest point and will processing to highest point or ideal point.